ANALISIS YURIDIS PELAKSANAAN PERMA NOMOR 2 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP (Studi Putusan Pengadilan Negeri Siak) - Dirgantara, Aditya; Deliana, Evi; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Prolonged social conflict, namely the decrease in courtesy and nobility in social relations, the weakening of honesty and trustworthiness in the life of the nation as well as the neglect of legal and regulatory provisions, and so on caused by various factors originating both from within and outside the country. One example we need to improve is social ethics and social participation in persons with disabilities or disabilities. As an Indonesian citizen, a person with a disability or disability has the same status, rights and obligations as other citizens. Persons with disabilities whose diverse groups are part of human resources whose rights need to be fulfilled, especially in terms of preparation and empowerment programs, intellectual quality, skill quality and othersÂ This research uses the typology of sociological legal research or also called non-doctrinal legal research, which specifically discusses the effectiveness of law. In this study the authors use the nature of descriptive research, because the authors describe how the Implementation of Riau Regional Regulation No 18 of 2013 concerning Protection and Empowerment of Persons with Disabilities in Riau Province. The results of research conducted by the author are, firstly the implementation of the implementation of Regional Regulation Number 18 of 2013 concerning the protection and Empowerment of Persons with Disabilities. Local governments are obliged to protect and guarantee the rights of people with disabilities without discrimination. It is recommended that with the high discrimination rate, every activity carried out must include all persons with disabilities in Riau Province in order to facilitate them in receiving information in any field such as the general publicKeywords: Implementation - Regional Regulation - Persons with Disabilities